Low-carbon operation strategy of AC/DC hybrid distribution network considering demand response and distributed robust game - XIAO Wenqiao; LIU Jichun (Diance yu yibiao)
The AC/DC hybrid distribution network has been widely studied due to its advantages such as flexible controllability and DC source-load friendly access, moreover, the increase of demand-side flexible resources makes the efficient utilization of demand response more diverse. On this basis, this paper proposes a low-carbon operation management strategy of AC/DC hybrid distribution network considering multi-type demand responses. Taking the power grid company as the leader, and the load aggregator and the electric vehicle agent as the follower, a master-slave game model is established consideringthe uncertainty of photovoltaics. In this model, the power grid company aims to maximize operating profit and minimize CO2 emissions, and considers the uncertainty of photovoltaic output to build a distributed robust optimization model for the AC/DC hybrid distribution network; followers maximize their own benefits to target in response to real-time electricity pricesand adjustuser load curtailment power and eletric vehicle charging power. The follower model is equivalent to the equilibrium constraint of the leader model by karush-kuhn-tucher (KKT) condition, the two-layer interactive game model is transformed into a single-layer distributed robust optimization model. Column and constraint generation (CCG) algorithm is used to decompose the model into master-slave problems to solve the model. The simulation results show that the proposed model can realize the low-carbon economic operation of the distribution network.